Budidaya Tanaman Jambu Mete Dan Pemasaran Dalam Meningkatkan Pendapatan Masyarakat Desa Hokeng Jaya - Yosef Moan Banda (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
The purpose of this study was to reveal the existence of cashew cultivation in increasing income, as well as the amount of community income from cashew sales and the factors supporting and inhibiting cashew cultivation. The focus of the problem is that cashew plants receive less attention from cashew farmers. This type of research is an integrated quantitative and qualitative research. An integrated quantitative and qualitative descriptive research approach. Collecting data with three techniques, namely "observation, questionnaires" and interviews. Data analysis used the highest percentage formula. From the results of the calculation according to the predetermined criteria, it can be seen that the proposed hypothesis was accepted, where the number of respondents who answered "Yes" was 69.5%. And those who answered "no" were 24.5%. This means that there is a significant relationship between cashew cultivation and increasing the income of cashew farmers in Hokeng Jaya Village, Wulanggitang District, East Flores Regency